Effect of nutrient and weed management on growth and yield of summer mungbean (Vigna radiata) - HASANAIN, MOHAMMAD; SHUKLA, D K; SINGH, RAJIV K; UPADHYAY, P K; SHEKHAWAT, KAPILA; RATHORE, S S; SINGH, V K (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted during summer 2016 at the GBPUA&T, Pantnagar, to study the effect of nutrients and weed management on productivity and profitability of summer mungbean [Vigna radiata (L.) Wilczek] in tarai region of Uttarakhand. The experiment was laid out in split-plot design keeping nutrient management practices, viz. F1: recommended dose of fertilizer (RDF; 18 kg N + 48 kg P2O5 + 24 kg K2O/ha), F2: half RDF + 2% urea spray at 40 days after sowing, F3: half RDF + 2% NPK mixture (12:32:16) spray at 40 DAS, F4: RDF + micronutrients (Zn EDTA 0.045% + boric acid 0.1% + ammonium molybdate 0.1%) spray at 20 and 40 DAS and F5: half RDF + micronutrients (Zn EDTA 0.045% + Boric acid 0.1% + ammonium molybdate 0.1%) spray at 20 and 40 DAS in main plots, and weed management practices, viz. W1: weedy check, W2: imazethapyr 10% SL @ 0.075 kg/ha as postemergence at 20 DAS, W3: pendimethalin 30% EC @ 1 kg/ha as pre-emergence + 1 hand weeding at 30 DAS and W4: pendimethalin 30% EC @ 1 kg/ha as PE + imazethapyr 10% SL @ 0.075 kg/ha as PoE at 20 DAS in sub plots with three replications. Significantly higher crop growth, yield attributes and grain yield (853 kg/ha) were found under F4 treatment than others and was comparable with F1. Similarly, highest crop growth, yield attributing characters and grain yield (1064 kg/ha) of summer mungbean was noticed with W3 treatment.